International Remittances, Migration, and Primary Commodities in FSGM - Snudden, Stephen (IMF Working Papers; Working Paper ;, 2017)
This paper adds international migration and remittances into the IMF's Flexible System of Global Models (FSGM). FSGM is a global general equilibrium model with endogenous primary commodity markets. A method to estimate the structural dynamics of major remitter regions is proposed. The dynamics of remittances and migration in FSGM are calibrated to be consistent with the main stylized facts of the empirical estimates. Structural disturbances pertinent to current global remittance flows are examined. These disturbances include disruptions to oil supply, output variation in Europe and the United States, labor nationalization policies in Saudi Arabia, and a global reduction in the cost to remit. The multilateral framework illustrates how remittance inflows need not originate from the region with the underlying economic disturbance but can arise from third party remitter regions affected by global commodity markets. The results also illustrate that the correlation of remittance inflows and the real GDP of labor-exporting economies can be either positively or negatively correlated. The evidence suggests that the behavioral incentive to migrate and remit cannot be deduced from correlations of real GDP and remittance inflows.